Polymeric antimicrobial membranes enabled by nanomaterials for water treatment - Zhu, J.; Hou, J.; Zhang, Y.; Tian, M.; He, T.; Liu, Jian; Chen, V. (Elsevier BV, 2018)
© 2018 Elsevier B.V. The application of polymer membranes in wastewater treatment and desalination is widespread. Nevertheless, the longstanding biofouling issue on membrane surface has garnered enormous attention within the scientific and industrial fields. Motivated by the recent development of nanocomposite membranes, the integration of biocidal nanomaterials with polymeric membranes has emerging as a promising strategy to mitigate biofouling. This review is aiming to encompass current nanomaterials and fabrication techniques, with highlights on the recent significant breakthroughs, in the field of antimicrobial nanocomposite membranes and imparts a comprehensive understanding of the strategic evolution in the design and construction approaches of antibacterial membranes. This review includes an exhaustive introduction of the antibacterial materials for membrane functionalization, including metal and carbon-based nanoparticles, organic antibacterial agents and bio-enzymes, together with their antibacterial mechanisms. Furthermore, we highlight the limitations in the current lab-based membrane antibacterial assay techniques, and discuss the challenges and prospective to link the antibacterial properties with the anti-biofouling behavior in practical applications.